PERAN NOTARIS DALAM MENDUKUNG REFORMASI BIDANG PELAYANAN PUBLIK DI KABUPATEN SLEMAN - , Endri Purwani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed at identifying the roles of Notary in supporting the reformation of public service affairs, identifying the inhibiting factors encountered by the Notary in providing public services and efforts carried out by the Notary in improving the quality of public services in Sleman Regency. The research employed empirical method. Data of the research included primary data and secondary data. The primary data were data obtained from respondentsâ interview and questionnaires. They were supported with secondary data obtained from library research in order to get primary and secondary law materials. The entire data were then analyzed qualitatively. The research result indicates that the roles of the Notary in supporting the reformation of public services in Sleman Regency have failed to meet the expectation. Such fact shows that the process of public service implementation carried out by the Notary has not fully guaranteed the reformation of public service affairs. The inhibiting factors encountered by the Notary include as follows: a. inadequate human resources in the Notary office